Case report: Highly differentiated endometrial adenocarcinoma that collided with uterine cervical carcinosarcoma - Fan, Xue; Hu, Haoyue; Liu, Yang; Tan, Songtao; Xie, Meng; Zhang, Fang (Frontiers in Medicine, 2023)
Uterine collision tumor is a rare pathological type composed of two or more malignant tumors. The components of these malignant tumors do not have histological mixing and are separated by the normal mesenchyme. Collision cancer is very rare, with uterine collision tumors being even rarer. Only a few cases have been reported in relation to uterine collision tumors. At present, there is no standard treatment guideline for uterine collision tumors, and a comprehensive treatment composed of surgery, radiotherapy, and chemotherapy is suggested. In this study, we report a 54-year-old female patient diagnosed with highly differentiated endometrial adenocarcinoma with cervical carcinosarcoma. The endometrial adenocarcinoma component invaded the deep myometrium (> 1/2 layer), involving the cervical glands and interstitium. The regional lymph node metastasis from endometrial adenocarcinoma was also detected. The patient underwent “transabdominal tumor cytoreduction (total hysterectomy + right adnexal resection + greater omentectomy + pelvic lymph node dissection + para-aortic lymph node dissection) + pelvic adhesion release.” In addition, she has completed adjuvant radiotherapy and chemotherapy. After reviewing previous reports of collision tumors in different positions of the uterus, we found that collision tumors between the cervix and uterine body are very uncommon. In addition, we have not found any reports on the metastasis of sarcoid components, no matter what the composition is.